Genetic diversity among five native Thai chickens and Khiew-Phalee chickens in lower-northern Thailand using mitochondrial DNA barcodes - PHROMNOI SIRIWADEE; LIKITTRAKULWONG WIROT; PUANGMALEE THANAPOL; NUCHCHANART WIRAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Siriwadee P, Wirot L, Thanapol P, Wirawan N. 2023. Genetic diversity among five native Thai chickens and Khiew-Phalee chickens in lower-northern Thailand using mitochondrial DNA barcodes. Biodiversitas 24: 1962-1970. Native chickens are an important biological resource in Thailand, with each breed having distinctive features. Khiew-Phalee chickens are a valuable investment in cultural wisdom and an invaluable Thai resource worthy of conservation. It is the royal rooster of Phraya Phichai Dab Hak. Due to a crisis concerning a sharp decline in the size of the Khiew-Phalee native chicken population, the identification of potential biomarkers is important for the determination of different chicken breeds for future planning. This study aimed to investigate the molecular identification of different native Thai chicken breeds based on mitochondrial DNA (mtDNA) barcodes, especially Khiew-Phalee chickens, which is difficult using the morphological examination. Partial sequences of 648 bp mtDNA control region fragments were determined for 53 specimens of six breeds of native Thai chickens (Khiew-Phalee, Thao Thong, Leung Hang Khao, Chee, Pra Dhu Hang Dam and Kai Jae). Genetic diversity was accessed based on the number of polymorphic sites, number of haplotypes, haplotype diversity, nucleotide diversity, and average number of differences. A phylogenetic tree was constructed based on maximum likelihood. The results showed that eighteen haplotypes were identified from 9 polymorphic sites with polymorphism between nucleotides 1074, 1107, 1109, 1177, 1213, 1214, 1268, 1276 and 1305. The haplotype diversity, nucleotide diversity, and the average number of differences for all chickens were 0.917, 0.00504 and 2.69086, respectively. All Khiew-Phalee chickens showed 7 haplotypes with 0.897 haplotype diversity, 0.00696 nucleotide diversity, and an average number of differences at 3.1795 clustered with other breeds in the phylogenetic tree. The findings indicated that the DNA barcoding gene is an effective method to identify the Khiew-Phalee and five other native Thai chicken breeds. It is a better choice for using molecular biology DNA barcoding to identify Thai native chicken breeds to plan for further conservation and development by the Department of Livestock Development of Thailand.